How physician relationships with neurotechnology companies impact clinical practice: interviews with physicians - Meredith V. Parsons; Judith M. Mwobobia; Erin D. Solomon; Michael Kudom-Agyemang; James M. DuBois; Tristan McIntosh (Frontiers in Neuroscience, 2026)
Introduction Physicians and neurotechnology companies each play a critical collaborative role when integrating neurotechnology into clinical practice. Physicians serve as gatekeepers and decision-makers in adopting neurotechnology, while companies often support the development, training, and maintenance of these devices. Relationships with industry require physicians to navigate complex clinical, ethical, and technological factors that affect their clinical roles. To understand physicians’ relationships with neurotechnology companies and facilitate responsible collaborations between the two, this study investigated physicians’ perspectives on these relationships and their influence on clinical practice. Methods Physicians ( N = 13) using neurotechnology to treat patients participated in a semi-structured interview exploring perspectives on neurotechnology companies and how these relationships affect their decision-making and approach to patient care. Interviews were recorded, transcribed, and coded using an inductive thematic approach. Results Physicians found their relationships with neurotechnology companies both beneficial and essential for device implementation in patient care. However, physicians acknowledged tensions that can arise when financial motivations of companies influence patient care. Company-sponsored research, events, marketing materials, and aggressive sales practices were viewed as potential sources of undue influence. But physicians also noted that reliable customer support, strong evidence of device safety and efficacy, streamlined implementation workflows, and devices that fit patients’ needs were all positive factors. Physicians expressed frustration about lack of transparency from companies regarding device troubleshooting and data sharing, high turnover in customer support or company leadership roles, and discontinuation of essential products or services. Additionally, physicians noted serious ramifications to patient care when a company discontinues a device or goes out of business without clear resolutions. Finally, physicians shared strategies for promoting objective clinical decision-making when working with companies, such as prioritizing patient wellbeing, using independent data sources, and conferring with colleagues to inform decisions. Conclusion Relationships between physicians and neurotechnology companies are essential for connecting devices to patient treatment. Physicians, companies, and hospitals all play a role in balancing financial motivations that intersect with patient care priorities. Findings from this study underscore the importance of ensuring that neurotechnological advancements prioritize patient well-being amid the complex partnerships between companies and physicians.